2022
DOI: 10.1021/acs.est.1c03047
|View full text |Cite
|
Sign up to set email alerts
|

In-Sewer Stability Assessment of Anabolic Steroids and Selective Androgen Receptor Modulators

Abstract: Wastewater-based epidemiology is a potential complementary technique for monitoring the use of performanceand image-enhancing drugs (PIEDs), such as anabolic steroids and selective androgen receptor modulators (SARMs), within the general population. Assessing in-sewer transformation and degradation is critical for understanding uncertainties associated with wastewater analysis. An electrospray ionization liquid chromatography mass spectrometry method for the quantification of 59 anabolic agents in wastewater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…This is consistent with initial cardarine and stenabolic concentrations found in spiked raw wastewater in our previous study. 10 In that study, cardarine losses through filtration and methanol content were observed, with no significant losses of the other biomarkers observed. 3′-Hydroxy stanozolol had the highest concentrations at t 0 (13− 13.8 μg/L) in unpreserved and Na 2 S 2 O 5 preserved wastewater (likely due to rapid deconjugation of its respective glucuronide) but had values close to the spiking level in HClpreserved wastewater (8.5−9.5 μg/L).…”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…This is consistent with initial cardarine and stenabolic concentrations found in spiked raw wastewater in our previous study. 10 In that study, cardarine losses through filtration and methanol content were observed, with no significant losses of the other biomarkers observed. 3′-Hydroxy stanozolol had the highest concentrations at t 0 (13− 13.8 μg/L) in unpreserved and Na 2 S 2 O 5 preserved wastewater (likely due to rapid deconjugation of its respective glucuronide) but had values close to the spiking level in HClpreserved wastewater (8.5−9.5 μg/L).…”
Section: Resultsmentioning
confidence: 68%
“…After vortexing, the vials were centrifuged at 4,750 rpm for 30 min at For statistical purposes, where at least one of the triplicate measurements was above the limit of detection (LOD), concentrations of the other measurements below the LOD and the limit of quantification (LOQ) were replaced with LOD/sqrt(2) and (LOD + LOQ)/2, respectively. 10 When all triplicate values were below the LOD, the concentration was set to 0.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations